(untitled) (Bangladesh Journal of Zoology, 2010)
The Shapla beel, an open beel having an area of 128 ha, is located in the Brahmanbaria district of northeastern region of Bangladesh. The study was carried out to document the water quality, icthyo- and planktonic diversity of beel ecosystem. Dissolved oxygen (DO) content ranged between 5.0 and 9.7 mg/L, pH fluctuated in the alkaline range (7.1-8.6) and free CO2 fluctuated between 1.6 and 18.9 mg/l. Total hardness and total alkalinity of the beel water fluctuated between 9.0 and 25.0 and 11.2 and 32.0 mg/l, respectively. A wide variation (11.8–42.2 x 103 cells/l) occured in the standing crop of total plankton; the contribution of phytoplankton to total plankton was high (93.37%). Phytoplankton diversity in the beel is represented by three groups in the order of dominance as follows: Chlorophyceae > Myxophyceae > Bacillariophyceae. A total of 51 fish species belonging to 36 genera, 20 families and one species of prawn occurred in the beel. A total of 13 fishing gear types was recorded from the beel. Fishing gears, like seine nets (moshari berjal, ghono berjal) and gill net (current jal) were identified as destructive to local fisheries. Kua fishing involved dewatering practice. A total of 11 species of aquatic weeds, belonging to 11 genera and 10 families, was identified from the beel. The eggs of Macrobrachium lamarrei were observed along with Najas najas vegetation during April-September. Bangladesh J. Zool. 38(1): 93-104, 2010